Revolutionary Climatology: Rings of Saturn, Ringed by Red Lightning - Sarah K. Stanley (Footprint)
Walter Benjamin’s concept of historical materialism is considered as a practice of media archaeology invented through literary montage and photo philosophy. The Arcades Project that facilitated this new research methodology involving a mobile archive. The main case involving architectural theory considers how Benjamin redeployed Sigfried Giedion and Laszlo Moholy-Nagy’s Building in France as a media environment, drawing upon its layout design, photo illustrations and textual systems. In terms of his urban writing, a reading of ‘A Berlin Chronicle’ considers how the diagram contributes to Benjamin’s archaeological methods, as a theory to generate site writing. Benjamin’s mode of media archaeology is then employed to map the arcades architecture onto the train stations and libraries in Berlin and Paris, sites that informed The Arcades Project. The final section assembles a set of citations as ‘Revolutionary Climatology’, thought-images as flashes of red lightning.